Hamstrings are most susceptible to injury during the late swing phase of sprinting - Chumanov, E. S.; Schache, A. G.; Heiderscheit, B. C.; Thelen, D. G. (British Journal of Sports Medicine, 2012)
It is well recognised that the hamstrings are susceptible to acute strain injury during high-speed running. However, the particular phase of the sprinting gait cycle at which hamstring injury occurs remains a debated topic. Video footage and athlete anecdotes have contributed to the discussion, but do not provide sufficient temporal resolution to fully answer the question. In this paper, we briefly review: (A) biomechanical data obtained from healthy athletes; (B) case studies of injuries during biomechanical experiments; and (C) clinical outcomes from intervention studies. We believe all of these support the premise that late swing phase is the likely time when the biarticular hamstrings are most vulnerable to injury. The first publications which considered the time of onset in the gait cycle for hamstring strains concluded that early stance was the highest risk period. The rationale proposed was that external joint moments were much higher in stance phases than swing because of the presence of high hip and knee joint reaction forces secondary to the ground reaction force (GRF). Ralph Mann's original argument has been rejected by many subsequent authors, perhaps because of the dogma that muscles probably strain during eccentric contractions. This is a widely held belief despite experimental muscle strains being able to be produced during concentric (shortening) contractions.